Diseño del sistema de abastecimiento de agua potable por bombeo, mediante energía solar fotovoltaica en el centro poblado Ganimedes, distrito de Moyobamba, provincia de Moyobamba, Región San Martín - Guevara Macedo, Alberto Yasir (2016)
The town of Ganymede located in the district and province of Moyobamba and San Martin Region, center does not have a drinking water system, so the water they consume not receive any treatment, causing waterborne diseases. Due to the negative slope between the water source and the town center, it is necessary for obtaining water using a system for pumping, but the power source for operating the system require the absence of electrical networks and fossil fuel due to the isolation that presents the community. Therefore an alternative that can counteract such an extent the problem with suffering today the population, which is the design of a potable water pumping by photovoltaic solar energy, thus saving themselves the unevenness is proposed that between the source and the town center recruitment. Given that seeks a source of energy that feeds the pumping system without the use of electricity and fossil fuel. To collect data to develop the thesis, we proceeded to locate sources of data. The direct testimony provided through interviews and surveys by users of the town, basic studies as topography, soil analysis, identification and analysis of the supply source. Following the collection of information it began to process data using computer programs, with reference to the parameters offered by Public Entities Country (Ministry of Housing, Construction and Sanitation), International Organizations (Pan American Health Organization) and various authors of good recognition. All for the purpose of having a good development in the field explorations, endowments, types of infrastructure in treatment units, design pump system that supplies the requirement of the design flow, design of distribution networks according to the rules